Revisions Policy for Official Statistics : A Matter of Governance - Carson, Carol; Khawaja, Sarmad; Morrison, Thomas (Washington, D.C. : International Monetary Fund, 2004)
This paper proposes a set of good practices for the revision of macroeconomic data. The authors argue that revisions are a routine part of disseminating quality data. Revisions are made not just to correct errors but also to incorporate better source data, update base periods, and make other improvements. It is argued, using country examples and views from policymakers and other users, that national statistical agencies should have explicit revisions policies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet